2024
DOI: 10.1556/2006.2023.00071
|View full text |Cite
|
Sign up to set email alerts
|

Ten years of research on the treatments of internet gaming disorder: A scoping review and directions for future research

Guang-Heng Dong,
Junhong Dai,
Marc N. Potenza

Abstract: BackgroundAlthough internet gaming disorder (IGD) has been listed in section III of the DSM-5 for approximately 10 years, the study of treatments for IGD remains in early stages. Nonetheless, a summary of findings to date and discussion of future research needs are warranted.MethodsThe current study reviewed scientific treatment studies with control groups and randomized controlled trials. We summarized the strengths and weaknesses of different treatment strategies and identified gaps in the research literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…Wang, Zheng, Zhou, et al, 2022). Disadvantageous decision-making in IGD may involve myopia in choosing immediately satisfying behaviours and not those with longer-term positive effects (G. Dong & Potenza, 2014;G. H. Dong et al, 2024;Y.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang, Zheng, Zhou, et al, 2022). Disadvantageous decision-making in IGD may involve myopia in choosing immediately satisfying behaviours and not those with longer-term positive effects (G. Dong & Potenza, 2014;G. H. Dong et al, 2024;Y.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang, Zheng, Zhou, & Dong, 2023), enhanced reward sensitivity (G. Dong, Huang, & Du, 2011;G. Dong, Li, Wang, & Potenza, 2017;G. H. Dong, Dai, & Potenza, 2024;Z.…”
Section: Introductionmentioning
confidence: 99%
“… 12 , 13 Despite increased understanding of the neurobiology of IGD, treatment development efforts in the behavioral, pharmacologic, and neuromodulatory domains have been arguably slower. 14 Previous studies have reviewed treatment strategies and their efficacy in treating IGD. 15 , 16 , 17 , 18 Although treatments are reported to decrease gaming craving or shorten gaming time, gaming recurrence after treatment may be high.…”
Section: Introductionmentioning
confidence: 99%
“…Dong et al. ( 15 ) reviewed treatment studies, including established approaches like CBT and newer options like pharmacotherapies and non-invasive brain stimulation (NIBS). They have suggested that CBT is the most extensively researched treatment for IGD and advice cautious implementation of medication-based approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Danielsen et al ( 14) examined treatment studies and proposed a positive impact of therapeutic interventions on gaming disorder, limited by small-study effects, potential publication bias, a restricted study sample, and a lack of standardization. Dong et al (15) reviewed treatment studies, including established approaches like CBT and newer options like pharmacotherapies and non-invasive brain stimulation (NIBS). They have suggested that CBT is the most extensively researched treatment for IGD and advice cautious implementation of medication-based approaches.…”
mentioning
confidence: 99%